The Biological and Medical Applications of Laser Light Abstract (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
The process of rapidly developing laser technology with the presence of the latest laser devices, which are constantly being introduced has become important in a variety of biological and medical fields. Low Level Laser Therapy has become of great importance for the treatment of soft tissue injuries and arthritis. An increase in cell proliferation and collagen after LLLT has already been observed in improving wound healing by improving inflammation, spread of fibroblasts, angiogenesis, collagen removal and tissue reconstruction. Photodynamic therapy (PDT) using laser beams is a proven treatment for cancer, other diseases, and bacterial infections resistant to antibiotics in wounds and burns.